Implicit measures of "wanting" and "liking" in humans. (October 2015) - Tibboel, Helen; De Houwer, Jan; Van Bockstaele, Bram
Highlights: We discuss different definitions of "wanting" and "liking" within Incentive Sensitization Theory. We discuss different implicit measures that have been used to examine these processes. We discuss whether it is reasonable to assume that these tests are valid. We review studies that inform us about this issue. We discuss the future potential of implicit measures in research on incentive sensitization. Abstract: Incentive Sensitization Theory (IST; e.g., Robinson and Berridge, 1993 . Brain Res. Rev., 18, 291;Robinson and Berridge, 2003 Trends Neurosci., 26, 507) suggests that a common dopamine system that deals with incentive salience attribution is affected by different types of drugs. Repeated drug use will sensitize this neural system, which means that drugs increasingly trigger the experience of incentive salience or "wanting". Importantly, Robinson and Berridge stress that there is a dissociation between drug "wanting" (the unconscious attribution of incentive salience) and drug "liking" (the unconscious hedonic experience when one consumes drugs). Whereas the former plays an essential role in the development and maintenance of drug addiction, the latter does not. Although this model was based mainly on research with non-human animals, more recently the dissociation between "wanting" and "liking" has been examined in humans as well. A widely used and promising means of studying these processes are behavioral implicit measures such as the Implicit Association Test (IAT), the Approach-Avoidance Task (AAT), different types of Stimulus-Response Compatibility (SRC) tasks, and Affective Simon Tasks (AST). IST makes the clear prediction that (1) there should be a positive correlation between indices of "wanting" (e.g., drug consumption) and implicit "wanting" scores. Similarly, there should be a positive correlation between indices of "liking" (e.g., various expressions of subjective pleasure) and implicit "liking" scores; (2) there should be higher "wanting" scores in substance abusers or frequent substance users compared to non-users or infrequent users, and there should be no differences in "liking" between these groups (or even less "liking" in frequent substance users); (3) manipulations of "wanting" should affect implicit "wanting" scores whereas manipulations of "liking" should affect implicit "liking" scores. However, studies that tested these hypotheses did not produce equivocal results. To shed light on these discrepancies, we first discuss the different definitions of "wanting" and "liking" and the different tests that have been used to assess these processes. Then, we discuss whether it is reasonable to assume that these tests are valid measures of "wanting" and "liking" and we review correlational, quasi-experimental, and experimental studies that inform us about this issue. Finally, we discuss the future potential of implicit measures in research on IST and make several recommendations to improve both theory and methodology.